An adaptive boost converter for low voltage piezoelectric energy harvesting. (25th September 2016) - Zhao, Yang; Wang, Kunpeng; Guan, Mingjie
ABSTRACT: This paper presents a two-stage adaptive boost converter with low-voltage starter for low voltage piezoelectric energy harvester. The adaptive technique can deal with a range of input voltages from the piezoelectric generator for required output voltages. The parameters of the converter including inductance, switching frequency, duty cycles and the input/output voltage are studied for conversion efficiencies. The experiment results show that a two-stage adaptive boost converter can achieve a conversion efficiency of 84.3%∼91.3% for a piezoelectric harvester in the considered low voltage range to charge an 1.5 V energy storage device.